Improving social function with real-world social-cognitive remediation in schizophrenia: Results from the RemedRugby quasi-experimental trial. Issue 1 (2020) - Dubreucq, Julien; Gabayet, Franck; Ycart, Bernard; Faraldo, Megane; Melis, Fanny; Lucas, Thierry; Arnaud, Benjamin; Bacconnier, Mickael; Bakri, Motassem; Cambier, Gentiane; Carmona, Florian; Chereau, Isabelle; et al.
Abstract: Background: Functional capacity (FC) has been identified as a key outcome to improve real-world functioning in schizophrenia. FC is influenced by cognitive impairments, negative symptoms, self-stigma and reduced physical activity (PA). Psychosocial interventions targeting FC are still under-developed. Methods: we conducted a quasi-experimental study evaluating the effects of an exercise-enriched integrated social cognitive remediation (SCR) intervention (RemedRugby [RR]) compared with an active control group practicing Touch Rugby (TR). To our knowledge, this is the first trial to date evaluating the effectiveness of such a program provided in a real-life environment. Results: Eighty-seven people with schizophrenia were included and allocated to either the RR group ( n = 57) or the TR group ( n = 30) according to the routine clinical practice of the recruiting center. Outcomes were evaluated at baseline and post-treatment in both groups and after 6 months of follow-up in the RR group using standardized scales for symptom severity, social functioning, self-stigma, and a large cognitive battery. After treatment we observed moderate to large improvements in social function (Personal and Social Performance Scale [PSP], p < 0.001, d = 1.255), symptom severity (Positive and Negative Syndrome Scale [PANSS] negative, p < 0.001, d = 0.827; PANSS GP, p < 0.001, d = 0.991; PANSS positive, p = 0.009, d = 0.594), verbal abstraction ( p = 0.008, d = 0.554), aggression bias ( p = 0.008, d = 0.627), and self-stigma (stereotype endorsement, p = 0.019, d = 0.495; discrimination experiences, p = 0.047; d = 0.389) that were specific to the RR group and were not observed in participants playing only TR. Effects were persistent over time and even larger between post-treatment and follow-up. Conclusions: Exercise-enriched integrated SCR appears promising to improve real-life functioning in schizophrenia. Future research should investigate the potential effects of this intervention on neuroplasticity and physical fitness.